Incidence of Injuries to Major Blood Vessels in the Lower Limb - Abd-alla, Mohammad A; Mohammad, Saad A (AL-Kindy College Medical Journal, 2009)
Background: Blood vessels injury is one of the mostcommon causes of medical emergencies that admitted tohospitals and at the same time it regarded as one of themost important causes of death. They may represent lessthan 15% of all injuries; they deserve special attentionbecause of their severe complications.Objective: The aim of the present study is to assessanatomically the injures of major arteries and veins in thelower limb with their management.Methods: The present study extended from April 2006 toFebruary 2007, in which 65 patients with lower limbvascular injury were examined in Emergency Departmentand Forensic Medicine Department of Tikrit TeachingHospital in Salah-Aldin governorate. Diagnosis was madeby clinical diagnosis alone, or in combination withangiography. Some surgical interferences as vascularrepair was carried out, but if not possible the interpositiongraft was used by great saphenous vein for vascularreconstruction.Results: The total cases were 65 patients (49 males and 16females), ranging from 16 years to 67 years with a meanage of 41.5±6.4 years. Penetrating trauma was the maincause of injury for 52 patients. Seventeen cases hadbilateral limbs vascular injuries. Arterial injuries were mostcommon in the femoral arteries, followed by the tibial andfinally the popliteal arteries. Vascular repair wereperformed in 16 cases, while in 11 cases great saphenousvein interposition graft were done. There were 17 casesassociated with venous injury, of which 11 cases hadsurgical vascular repair, and 6 had vein graft interposition.There were concomitant femur fractures in 2 cases, fibulafractured in 3, tibia fractured in 1 and the foot bonesfractured in 3.Conclusion: Lower limb vascular injured patient should betransferred to vascular surgery centers as soon as possible.After first aid management, anticoagulant treatment may bestarted post operatively to prevent the propagation of thethrombosis. Early fasciotomy is done if there is anysuspicion of occurrence of compartment syndrome.